2012
DOI: 10.1149/2.014204jes
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Atomic Layer Deposited HfO2Films on Ge Substrates Depending on Process Temperatures

Abstract: The effect of deposition temperature and post deposition annealing (PDA) on the electrical properties of HfO 2 films grown on a Ge substrate by atomic layer deposition (ALD) was investigated. The HfO 2 films deposited at 280 • C (280 • C-HfO 2 ) showed a large capacitance-voltage (C-V) hysteresis, but it was significantly reduced at 200 • C (200 • C-HfO 2 ). Further reduction of deposition temperature to 160 • C resulted in the abrupt increase of C-V hysteresis. The reduction of C-V hysteresis was originated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…[4][5][6][7] Several papers reported that carbon contents in the HfO 2 films on Si substrate increased with decreasing deposition temperature, causing the stabilization of the tetragonal (or cubic) phase. 8,9 However, atomistic mechanism for such stabilization is still under debate. Fischer et al reported that the tendency to stabilize the tetragonal phase is strongly dependent on the kind of dopant used, including Si, C, Ge, Ti, Se, and Ce, and that their ionic size plays a crucial role in the stabilization mechanism.…”
mentioning
confidence: 99%
“…[4][5][6][7] Several papers reported that carbon contents in the HfO 2 films on Si substrate increased with decreasing deposition temperature, causing the stabilization of the tetragonal (or cubic) phase. 8,9 However, atomistic mechanism for such stabilization is still under debate. Fischer et al reported that the tendency to stabilize the tetragonal phase is strongly dependent on the kind of dopant used, including Si, C, Ge, Ti, Se, and Ce, and that their ionic size plays a crucial role in the stabilization mechanism.…”
mentioning
confidence: 99%
“…The average ΔVFB of p-HfO2/a-HfO2 and p-HfO2 was 0.28 V and 1.46 V, respectively. Therefore, the additional a-HfO2 layer deposited on p-HfO2 results in the reduction of VFB by ~ 1.18 V, and exhibits lower ΔVFB in comparison with the reported value of a Ge gate stack with a-HfO2 layer [32].…”
Section: Resultsmentioning
confidence: 51%
“…Although other amorphous high-k films can be applied as a capping layer, it is reported that the interface dipoles at the boundary of different oxide layers can cause additional hysteresis [28,29]. Even compared with the direct diffusion of Ge atoms into the a-HfO2 gate-dielectric, the proposed p-HfO2/a-HfO2 dielectric shows better interface quality [32]. Therefore, the proposed p-HfO2 dielectric capped by a-HfO2 can exhibit improvement of interface quality and reduction of leakage current.…”
Section: Resultsmentioning
confidence: 99%
“…Dielectric layer HfO2’s thickness is 2 nm and εHfO2 is 25 31 . Note that εHfO2 is related to the manufacturing process of the film 31 , 43 , 44 . For thickness of 2 nm, the breakdown voltage of HfO2 is 2.6 V. Even if εHfO2 drops to 11 due to the CVD and ALD process, the corresponding voltage in the off state calculated from Equations (3) and (4) do not exceed the breakdown voltage.…”
Section: Resultsmentioning
confidence: 99%
“…31 Note that ε HfO 2 is related to the manufacturing process of the film. 31,43,44 For thickness of 2 nm, the breakdown voltage of HfO 2 is 2.6 V. Even if ε HfO 2 drops to 11 due to the CVD and ALD process, the corresponding voltage in the off state calculated from Equations ( 3) and ( 4) do not exceed the breakdown voltage. Therefore, the deposition thickness and the ε HfO 2 of the film can be compensated by changing the voltage.…”
Section: Modulation Bandwidthmentioning
confidence: 99%